ANALISIS RISIKO SISTEMATIS DAN RISIKO TIDAK SISTEMATIS TERHADAP EXPECTED RETURN SAHAM DALAM PEMBENTUKAN PORTOFOLIO OPTIMAL INDEKS SAHAM LQ45 - Mochamad Effendi; Hidayat Hidayat; Muninghar Muninghar (Jurnal Manajerial Bisnis, 2017)
This study aims to determine the description of systematic risk, not systematic risk of expected share return. In addition, to determine the effect of systematic risk and risk not systematic either partially or simultaneously to the expected return of shares in the formation of an optimal portfolio of LQ 45 stock index. Data analysis technique used in this research is simple linear regression. The calculator uses the SPSS program. The results of the data analysis show that among the 45 companies listed in the LQ-45 index that meet the criteria in the formation of an optimal portfolio viewed from systematic risk and systematic risk there are only six companies. The six companies are PT AKRA Corporindo Tbk, PT Bank Central Asia Tbk, PT Indofood CBP Sukses Makmur Tbk, PT Kalbe Farma Tbk, PT Telekomunikasi Indonesia (Persero) Tbk and PT Unilever Indonesia Tbk so as to obtain optimal portfolio of shares of 57. Systematic risk and risk not systematically partially significant effect on the expected return of stock in forming optimal portfolio of LQ-45 stock index. Systematic risk and systematic risk are not simultaneously significant to the expected return of stock in forming an optimal portfolio of LQ 45 stock index.